Peran Guru dalam Mengembangkan Keterampilan Berbicara Anak di Taman Kanak-kanak Pembina 01 Air Haji Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan - Anjani Putri, Popi; Yulsyofriend, Yulsyofriend (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
Speaking was a skill to give expretion, statetement, and convey thoughts, ideas, and feels by pronouncing articulation sounds or words. Speaking skills need to be trained from and early age, because speaking skills are very important for children so that they are easy to speak regularly and skillfully in the future, because speaking is one of the main communication tools. This research purpose to shown the planning, implementation, and evaluation of the teacher's role in developing children's speaking skills at Kindergarten Pembina 01 Air Haji, Linggo Sari Baganti District, Pesisir Selatan District. In the research used a method of qualitative with a approach in descriptive. This research uses techniques for data collection in shape of of observation, interviews, and documentation. The technique for data analysis was conducted by data collected, data reduced, data presented and make conclusions. According on the research result that has been conducted, it is said that the lesson plan in developing children's speaking skills is planned from the teacher in accordance with the RPPH and also the teacher uses the question and answer method, storytelling method, singing in developing children's speaking skills. The media used by the teacher is picture media, hand puppet media with fun learning strategies for children. And also the evaluation was conducted by the teacher to look development aspect in children regarding the level of children's speaking skills development.